Identification and Evaluation of Drug-related Problems Associated with Angiotensin Converting Enzyme Inhibitor Use - Nadia Alrawaiq,; Ekhlass Nassr,; Alaa Matr, (AlQalam Journal of Medical and Applied Sciences, 2025)
Drug-related problems (DRPs) are relatively common among hospitalized patients, causing detriment to themselves and increased healthcare costs. Characterizing such problems allows for the development of remedial strategies aimed at minimizing their frequency and ensuring higher medication safety for the patients involved. This study focuses on inpatients receiving ACE inhibitors who are admitted to internal medicine wards, as the literature has a gap in this respect. Consequently, we provide a comprehensive assessment of the DRPs associated with the use of ACE inhibitors use hospitalized patients in the Sebha Medical Centre. Ethical approval was granted for the study, which was conducted for two months, during which 175 patient medical records were collected and reviewed. A specialized clinical pharmacist identified a total of 186 DRPs and classified these, revealing an average of 1.06 problems per patient. The most common DRPs were identified as drug interactions (78%), adverse drug reactions (17%), improper dose (3%), and improper indication (2%). Drug interaction problems were significantly associated with patients taking several medications (P ˂0.05). The high prevalence of DRPs among hospitalized patients in the Sebha Medical Center is alarming. This study highlights the importance of clinical pharmacy services to help identify and reduce DRPs. Additionally, patients with multiple medical conditions and patients using multiple medications should be closely assessed for DRPs.